System zarządzania strategicznego oparty na zrównoważonej karcie wyników - Pietrzak, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the idea of strategic management system (SMS) based on the balanced scorecard The key issues of such a system are organizational structure (respoonsibilities), strategic reviews and audits and documentation. The paper describes these issues. Preparing SMS formalizes the process of executing strategy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 333-342